Spatially-controlled laser-induced decoration of 2D and 3D substrates with plasmonic nanoparticles - Bashouti, M. Y.; Povolotckaia, A. V.; Povolotskiy, A. V.; Tunik, S. P.; Christiansen, S. H.; Leuchs, Gerd; Manshina, A. A. (RSC Advances, 2016)
We demonstrate a new approach which can be used for targeted imparting of plasmonic properties for a wide range of different substrates (transparent and non-transparent) which may have any 2D or 3D topological structure created independently in a prior step with some other technology.
EAM Import::2019-03-13